2014
DOI: 10.1016/j.crohns.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Total soluble and endogenous secretory receptor for advanced glycation endproducts (RAGE) in IBD

Abstract: Although total sRAGE varied with activity in UC, esRAGE concentrations correlated inversely with endoscopic disease activity and CRP levels in both UC and CD. Additional studies are required to further define the significance of sRAGE and esRAGE in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Similar to inflammatory bowel disease in humans,136 serum sRAGE concentrations are significantly decreased in dogs with CIE but do not correlate with the severity of clinical signs, overall histologic lesions, or outcome 27. However, a weak correlation exists between serum sRAGE concentrations and histologic duodenal lesions (Cabrera Garcia, personal communication 2018).…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to inflammatory bowel disease in humans,136 serum sRAGE concentrations are significantly decreased in dogs with CIE but do not correlate with the severity of clinical signs, overall histologic lesions, or outcome 27. However, a weak correlation exists between serum sRAGE concentrations and histologic duodenal lesions (Cabrera Garcia, personal communication 2018).…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
“…135 The lack of a correlation between serum sRAGE and S100A12 concentrations suggests that sRAGE is a nonspecific decoy receptor in dogs. 27 Similar to inflammatory bowel disease in humans, 136 [IL]-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12p40, IL-17, IL-18, IL-23, IL-25, IL-33, IFN-γ, TNF-α, and TGF-β1) in dogs with CIE, [137][138][139][140][141][142][143] all of which do not support a Th1 nor Th2 polarization as described for inflammatory bowel diseases in humans. 144,145 There also is no evidence of a Th17 signature in dogs with CIE. 146,147 One problem with using cytokines as biomarkers in dogs is that there are many cytokine assays available.…”
Section: Soluble Receptor For Advanced Glycation End Productsmentioning
confidence: 99%
“…115 A number of small studies have attempted to correlate blood soluble RAGE levels with the presence and activity of IBD with conflicting results. 55,[116][117][118][119] In addition to RAGE, DAMP regulatory pathways may play a role in IBD. The TREM-1 (triggering receptor expressed on myeloid cells 1) is an immunoglobulin present on monocytes and neutrophils that upregulates DAMP-PRR-mediated signaling.…”
Section: Damp Pathways In Ibdmentioning
confidence: 99%
“…Because these isoforms lack a transmembrane domain, they are secreted and act as decoy receptors. Indeed, sRAGE has been shown to prevent or reverse RAGE signals in experimental models of diabetic atherosclerosis, wound healing, amyloidosis, and colitis 36 39 . In addition, Zhang and colleagues reported that sRAGE treatment significantly attenuates the neutrophilic inflammation and pathological changes in the LPS-induced murine model of acute lung injury, suggesting that sRAGE may be secreted as a decoy receptor and contributes to the suppression of excessive inflammatory responses during actual lung injury 40 .…”
Section: Discussionmentioning
confidence: 99%